2021
DOI: 10.3390/vaccines9111231
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ Willingness to Vaccinate Their Children against Childhood Diseases and Human Papillomavirus: A Cross-Sectional Study on Vaccine Hesitancy in Malawi

Abstract: Background: Vaccines are among the most effective and cost-efficient public health interventions for promoting child health. However, uptake is considerably affected by vaccine hesitancy. An example is Malawi, with a decline in second vaccine doses and the highest cervical cancer incidence and mortality rate in Sub-Saharan Africa. Understanding vaccine hesitancy is especially important when new vaccines are introduced. This study explores factors contributing to vaccine hesitancy for routine childhood immuniza… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 57 publications
(73 reference statements)
2
33
0
Order By: Relevance
“…Therefore, the knowledge gap that created the belief that immunization can prevent all childhood diseases, including malaria or COVID-19, might lead to a lack of confidence in the efficacy of vaccines to prevent VPD and in the healthcare system. The knowledge gap found in this study is similar to that found in Sub-Saharan Africa (SSA), where the population has misconceptions about vaccines [ 21 , 22 , 23 , 24 ]. More work is still needed in SSA to improve the knowledge of VPD and determine the best communication method for vaccination information.…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, the knowledge gap that created the belief that immunization can prevent all childhood diseases, including malaria or COVID-19, might lead to a lack of confidence in the efficacy of vaccines to prevent VPD and in the healthcare system. The knowledge gap found in this study is similar to that found in Sub-Saharan Africa (SSA), where the population has misconceptions about vaccines [ 21 , 22 , 23 , 24 ]. More work is still needed in SSA to improve the knowledge of VPD and determine the best communication method for vaccination information.…”
Section: Discussionsupporting
confidence: 78%
“…It is expected that the 5C will predict vaccination intention and behavior as described above. Moreover, we expected the three additional variables (religion, masculinity and rumor/misinformation) to negatively in uence vaccination intention and behavior [31,32]. Also, intention (T1) is expected to predict the mother's vaccination behavior (T2).…”
Section: Study Aimmentioning
confidence: 99%
“…Rumor/misinformation affects the perception and attitude of people, especially as social media continues to dominate the ampli cation of vaccine misinformation, thereby affecting vaccination demand [31,32,42]. It makes the inclusion even more relevant.…”
Section: Rumor/misinformationmentioning
confidence: 99%
“…The study implementation instruments were interview guides. The guide comprised the following themes and topics, based on validated measures in the same setting [ 26 , 27 , 30 ]: knowledge of immunisation (“What do you know or think about immunisation?”); knowledge of HPV/cervical cancer (“Do you know or have you heard about cervical cancer and/or the HPV vaccine?”); attitude toward childhood RI and the HPV vaccine (“Do you think childhood RI is an important topic for you and/or your community?…How?” and “What do you think about the HPV vaccine and the target group?…Why do you think that way?”); barriers against childhood RI (“Do you know about vaccine hesitancy and what are the reasons for low childhood immunisation demand?…Please describe why”); barriers against HPV vaccine acceptance (“Do you know about hesitation against HPV vaccine?…If so, what are they, among whom are they, and why?”). These measures have been tested across different settings in SSA and has generated high reliability, especially in Malawi.…”
Section: Methodsmentioning
confidence: 99%